The effect of being Protestant on entrepreneurial choice - Michael Wyrwich (Friedrich Schiller University Jena, 2018)
This brief research note identifies a causal effect of being Protestant on entrepreneurial choice.
Keywords: L26; Z1; Z12; 330; Religion; Protestantism; Entrepreneurship